The impact of virtual reality in the motion picture industry regarding brand coolness, emotional responses, and WOM - Rodrigues, Mariana de Oliveira Berga (2020)
The main goal of the present dissertation is to understand how virtual reality impacts the motion picture industry regarding the constructs of brand coolness, empathy, sympathy, and word-ofmouth in comparison with the traditional 2D screens, while also considering the importance of the movie content. Thus, the study consists of a quantitative research which is based on a factorial research design, considering the interactions between the two technological formats (2D and VR) and the two movies (“Crow: The Legend” and “Is Anna Ok?”). The chosen methodology allows us to determine that a movie experienced in VR has more positive scores regarding brand coolness, emotional responses (empathy and sympathy), and WOM, than when the same movie is presented in 2D screens. However, the Two-Way ANOVA analysis also determines that the movie content itself affects brand coolness perceptions and sympathy responses more than the technological format. Meaning that the story content has a higher influential power on how the movie is perceived by the audience when considering these constructs than the technological format. On the other hand, regarding empathy responses and WOM, the technological format proved to have a higher impact than the story content. Additionally, further analysis allowed us to understand how brand coolness is perceived regarding movies and how emotional responses to movies influence the audience’s attitudes and coolness perceptions. The theoretical and managerial implications of these findings are also explained.